Najstarsze tłumaczenia tekstów biblijnych na język kaszubski - Sikora, Adam Ryszard (Poznańskie Studia Teologiczne, 2008)
This paper discusses translations of biblical passages into Kashubian which originated in Evangelical circles between the 16lh and 19th centuries. Although the tradition of translation dates back to the 16th century, translation of the entire Bible, or at least one complete biblical book, which would have originated in this particular environment has not been preserved. Presumably it never existed. The oldest translations of biblical texts into Kashubian were generally based on the German language. The first printed book with texts in Kashubian included, among others, eleven works defined as Psalms and a range of short passages originating both from the Old Testament and the New Testament. This very book was the Simon Krofey’s Hymnal published in Gdańsk in 1586. Translation of The Small Catechism of Martin Luther came out approximately half a century later, and similarly to the Krofey’s Hymnal it included many biblical passages. However, the biggest collection of biblical texts which has survived is dated for the turn of the 17th and 18* centuries. These texts are found in the so-called Smoldzinian Perikopes, containing lessons and Gospels for all Sundays and church holidays. Many smaller passages of the older translation of biblical texts represent only occasional translations of biblical passages incorporated in other religious texts. The first intended and methodical translation of texts from the Sacred Scripture into Kashubian was the collection of so-called Smoldzinian Perikopes. Research conducted on these translations allows to conclude that although authors of these translations did not translate from original texts, but in most cases from the German language, their translations of the Bible are characterised by a high degree of faithfulness to the thought of original texts. Moreover, accuracy and efforts to make the texts comprehensible and literary beautiful grant their authors the best testimony.